Chronic Sleep Fragmentation Mimicking Sleep Apnea Does Not Worsen Left-Ventricular Function in Healthy and Heart Failure Mice - Cabrera-Aguilera, Ignacio; Benito, Begoña; Tajes, Marta; Farré, Ramon; Gozal, David; Almendros, Isaac; Farré, Nuria (Frontiers in Neurology, 2020)
Aims: Obstructive sleep apnea (OSA) has been associated with heart failure (HF). Sleep fragmentation (SF), one of the main hallmarks of OSA, induces systemic inflammation, oxidative stress and sympathetic activation, hence potentially participating in OSA-induced cardiovascular consequences. However, whether SF per se is deleterious to heart function is unknown. The aim of this study was to non-invasively evaluate the effect of SF mimicking OSA on heart function in healthy mice and in mice with HF. Methods and Results: Forty C57BL/6J male mice were randomized into 4 groups: control sleep (C), sleep fragmentation (SF), isoproterenol-induced heart failure (HF), and mice subjected to both SF+HF. Echocardiography was performed at baseline and after 30 days to evaluate left ventricular end-diastolic (LVEDD) and end-systolic (LVESD) diameters, left ventricular ejection fraction (LVEF) and fraction shortening (FS). The effects of SF and HF on these parameters were assessed by two-way ANOVA. Mice with isoproterenol-induced HF had significant increases in LVEDD and LVESD, as well as a decreases in LVEF and FS (p = 0.013, p = 0.006, p = 0.027, and p = 0.047, respectively). However, no significant effects emerged with SF (p = 0.480, p = 0.542, p = 0.188, and p = 0.289, respectively). Conclusion: Chronic SF mimicking OSA did not induce echocardiographic changes in cardiac structure and function in both healthy and HF mice. Thus, the deleterious cardiac consequences of OSA are likely induced by other perturbations associated with this prevalent condition, or result from interactions with underlying comorbidities in OSA patients.